1993
DOI: 10.1152/ajpheart.1993.264.5.h1337
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced single-channel K+ current in arterial membranes from genetically hypertensive rats

Abstract: Arterial smooth muscle from hypertensive rats shows an increased membrane permeability to K+ that depends on Ca2+ influx. To define the mechanism of this membrane alteration, we tested the hypothesis that Ca(2+)-dependent K+ current (IK(Ca)) is increased in arterial muscle membranes from genetically hypertensive rats. Single-channel K+ currents measured in cell-attached and inside-out aortic membrane patches from spontaneously hypertensive rats (SHR) were compared with those from normotensive Wistar-Kyoto rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 0 publications
7
58
2
Order By: Relevance
“…The contractions evoked by TEA, iberiotoxin, or charybdotoxin were significantly higher in SHR MA than in WKY, suggesting an increased functional activity of K Ca channels in the SHR vessels. This is consistent with the report by Rusch et al (1992) in SHR aorta and that by Asano and Nomura (2002) in SHR femoral, mesenteric, and carotid artery, and in SHR aortic smooth muscle cells (England et al, 1993). In a separate study, we have performed a Western blot analysis of the large conductance K Ca channel protein in the MA from SHR and WKY, and found that K Ca was increased in SHR (unpublished data), similar to a previous report using SHR aorta (Liu et al, 1997).…”
Section: Discussionsupporting
confidence: 94%
“…The contractions evoked by TEA, iberiotoxin, or charybdotoxin were significantly higher in SHR MA than in WKY, suggesting an increased functional activity of K Ca channels in the SHR vessels. This is consistent with the report by Rusch et al (1992) in SHR aorta and that by Asano and Nomura (2002) in SHR femoral, mesenteric, and carotid artery, and in SHR aortic smooth muscle cells (England et al, 1993). In a separate study, we have performed a Western blot analysis of the large conductance K Ca channel protein in the MA from SHR and WKY, and found that K Ca was increased in SHR (unpublished data), similar to a previous report using SHR aorta (Liu et al, 1997).…”
Section: Discussionsupporting
confidence: 94%
“…Our finding that the altered membrane potential observed in SHR carotids is not due to impaired K ϩ channels agrees with previous reports based on patch-clamp measurements of K ϩ currents in SHR 18 and in aldosterone-induced hypertensive rats 19 . However, these findings contrast with a report of decreased K Ca currents in angiotensin-induced hypertension 20 .…”
Section: Discussionsupporting
confidence: 93%
“…79 Only recently, however, has the TEA-sensitive, Ca 2+ -activated "maxi-K + channel" been identified as the likely molecular pathway for this elevated current. 8 At the same membrane potential and [Ca],, this K + channel type appears to show a higher open state probability in cell-attached and inside-out aortic membrane patches from adult SHR compared with WKY rats. 8 However, despite clarification of its single-channel nature, the link between high blood pressure and the etiology of elevated arterial K + current remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…8 At the same membrane potential and [Ca],, this K + channel type appears to show a higher open state probability in cell-attached and inside-out aortic membrane patches from adult SHR compared with WKY rats. 8 However, despite clarification of its single-channel nature, the link between high blood pressure and the etiology of elevated arterial K + current remains unclear. With regard to genetic hypertension, only K + flux in vascular membranes from adult SHR has been measured, 5 and therefore it is unknown whether K + channel changes are a consequence of elevated blood pressure or precede blood pressure elevation as an expression of genetic diversity between rat strains.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation